PENGARUH GAYA KOMUNIKASI KEPEMIMPINAN PEREMPUAN TERHADAP PERSEPSI MASYARAKAT : Survei Pada RW 10/ RT 03 Kelurahan Babakan Pasar - VIKA MARLINA (2020)
Communication style is specialized interpersonal behavior that is used in certain situations. A leader must have other advantages from its members such as morals, enthusiasm, intelligence, sensitivity to the environment, perseverance, responsibility, and resolving conflicts and making policies. The task of a leader is indeed quite difficult and not easy, especially for female leaders because there are still many negative community perceptions of women's leadership. Women are considered to have weak and indecisive communication styles. This study uses symbolic interaction theory. The approach in this study is a quantitative approach to the survey method using a questionnaire. The population in this study is the people in RW 10 / RT 03, amounting to 350 people. The population was chosen because this area has a place of tourism called the labyrinth village so that this area is often visited by Mrs. Rena. The sample in this study was 78 respondents using simple random sampling technique. The results of the correlation test are the X variable (communication style) to the Y variable (people's perception) showing that there is a very strong correlation of 0.886. The results of the determination coefficient test are known to be 78.4%. The results of the hypothesis test is t count 16,644> t table 1,665, it can be concluded that H0 is rejected and Ha is accepted, which means that there is an influence of women's leadership communication style on community perceptions of RW 10 / RT 03 kelurahan babakan pasar. keyward : Communication Style, Women's Leadership, Perception, Society, Symbolic Interaction Theory.